Prognostic significance of computed tomography defined ascites in advanced gastric cancer - Cheong, Jin Cheol (The Korean Surgical Society, 2012)
PURPOSE: The aim of this study was to investigate the clinicopathologic features and prognosis in patients with computed tomography (CT) findings of ascites, with a focus on the correlation with peritoneal carcinomatosis. METHODS: This study included a total of 157 patients who underwent surgery for advanced gastric cancer from 2003 to 2008 at the Department of Surgery, Hallym University Kangdong Sacred Heart Hospital, Seoul, Korea, which were analyzed retrospectively. RESULTS: Fourteen patients (8.9%) presented ascites on their CT scan. Among them, 10 patients had peritoneal carcinomatosis, and showed significant difference with CT ascites positive group in the incidence of peritoneal carcinomatosis. The presence of CT ascites was significantly correlated with pathologic T stage, tumor size, histologic type, CT T and N stages, CT peritoneal nodularity and curability of surgery, statistically. The prognosis of CT ascites positive group was much poorer in the total advanced gastric cancer patients (P < 0.001), as well as in patients with pathologic T4 (P = 0.002). Also in patients without peritoneal carcinomatosis, CT ascites positive subgroup tended to have a worse prognosis than CT ascites negative subgroup (P = 0.086). Tumor size, CT T and N stages and the presence of CT peritoneal nodularity and ascites influenced the prognosis significantly; among which, if a tumor size larger than 5 cm, CT T4 stage and the presence of CT ascites were identified as independent prognostic factors. CONCLUSION: The presence of ascites was closely associated with peritoneal metastasis, and was the most significant independent prognostic factor in advanced gastric cancer in the present study.